Isoprenoid biosynthesis regulation in poplars by methylerythritol phosphate and mevalonic acid pathways - Movahedi, Ali; Wei, Hui; Pucker, Boas; Ghaderi-Zefrehei, Mostafa; Rasouli, Fatemeh; Kiani-Pouya, Ali; Jiang, Tingbo; Zhuge, Qiang; Yang, Liming; Zhou, Xiaohong (Frontiers in Plant Science, 2022)
It is critical to develop plant isoprenoid production when dealing with human-demanded industries such as flavoring, aroma, pigment, pharmaceuticals, and biomass used for biofuels. The methylerythritol phosphate (MEP) and mevalonic acid (MVA) plant pathways contribute to the dynamic production of isoprenoid compounds. Still, the cross-talk between MVA and MEP in isoprenoid biosynthesis is not quite recognized. Regarding the rate-limiting steps in the MEP pathway through catalyzing 1-deoxy-D-xylulose5-phosphate synthase and 1-deoxy-D-xylulose5-phosphate reductoisomerase (DXR) and also the rate-limiting step in the MVA pathway through catalyzing 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR), the characterization and function of HMGR from Populus trichocarpa (PtHMGR) were analyzed. The results indicated that PtHMGR overexpressors (OEs) displayed various MEP and MVA-related gene expressions compared to NT poplars. The overexpression of PtDXR upregulated MEP-related genes and downregulated MVA-related genes. The overexpression of PtDXR and PtHMGR affected the isoprenoid production involved in both MVA and MEP pathways. Here, results illustrated that the PtHMGR and PtDXR play significant roles in regulating MEP and MVA-related genes and derived isoprenoids. This study clarifies cross-talk between MVA and MEP pathways. It demonstrates the key functions of HMGR and DXR in this cross-talk, which significantly contribute to regulate isoprenoid biosynthesis in poplars.